Synthesis 1,2-bis ((3-methylbut-2-en-1-yl)oxy) -4-(((3methylbut-2-en-1-yl)oxy)methyl)benzene - Ahmad Rizqi Alima Fabri; Mardi Santoso (IPTEK Journal of Proceedings Series, 2020)
Kojic acid and arbutin are materials that are used to inhibit melanogenesis, but in their development, these two compounds have an adverse effect on the skin. 3,4-dihydroxybenzaldehyde is a simple phenol compound whose derivatives are used as flavorers and fragrance. The research carried out aims to obtain 3,4-dihydroxybenzaldehyde derivatives in the form of 1,2-bis((3-methylbut-2-en-1-yl)oxy) 4-(((3-methylbut-2-en-1-yl)oxy)methyl)benzene which is estimated based on its structure is able to inhibit melanogenesis, and has a similar structure to the commercial fragrance of methyl diantilis. The synthesis of the target compound is carried out in three step. The first step involves the alkylation of 3,4-dihydroxybenzaldehyde with 3,3-dimethylalyl bromide and sodium hydride in the dimethylformamide solvent at room temperature to obtain 3,4-bis ((3-methylbut-2-en-1-il) benzaldehyde. Reduction of formyl 3,4-bis((3-methylbut-2-en-1-il) benzaldehyde which is carried out in the second stage with sodium borohydride in ethanol obtained 3,4-bis((3-methylbut-2-en-1-yl)oxy)phenyl)methanol. Etherification 3,4-bis ((3-methylbut-2-en-1-il)oxy)phenyl)methanol with 3,3-dimethylalyl bromide and sodium hydride in the solvent dimethylformamide at room temperature is obtained target compound 1,2-bis((3-methylbut-2-en-1-il)oxy)-4-(((3-methylbut-2-en-1 il)oxy)methyl)benzene whose structure is determined by NMR, mass, and IR spectroscopy.